2019
DOI: 10.3168/jds.2018-14578
|View full text |Cite
|
Sign up to set email alerts
|

Associations between immune competence, stress responsiveness, and production in Holstein-Friesian and Holstein-Friesian × Jersey heifers reared in a pasture-based production system in Australia

Abstract: The objectives of this study were to assess antibody and cellular immune responses in first-lactation dairy heifers reared under a pasture-based production system and to investigate associations between immune competence and stress responsiveness, health, and productivity. A commercial vaccine was used to induce antibody and cellular immune responses and, based on measured responses, animals were classified as above average, average, and below average for each trait independently and in combination (overall im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Secondly, an alternative approach to measuring resilience has been used by Hine and colleagues (Aleri et al 2019;Hine et al 2019;Hine et al 2021;Hine et al 2022). These authors have measured the strength of the immune response during the stress of routine husbandry practices such as weaning of beef calves and lambs bred and raised in a pasture-based production system.…”
Section: Measuring Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, an alternative approach to measuring resilience has been used by Hine and colleagues (Aleri et al 2019;Hine et al 2019;Hine et al 2021;Hine et al 2022). These authors have measured the strength of the immune response during the stress of routine husbandry practices such as weaning of beef calves and lambs bred and raised in a pasture-based production system.…”
Section: Measuring Resiliencementioning
confidence: 99%
“…This approach measures the absolute level of performance of the immune system, termed immune competence, under stress rather than characteristics of response kinetics (Hine et al 2019;Hine et al 2022) and complements a large body of work on associations between immune competence and disease outcomes in livestock (for reviews see Wilkie and Mallard 1999;Hine et al 2015;König and May 2019;Bai and Plastow 2022). Immune competence measured in dairy heifers during routine husbandry is negatively correlated with cortisol responses (Aleri et al 2019) and thus immune competence may be an indicator of resilience. In support of this conclusion is the observation that protective host responses to heat stress are stronger in cows with high immune competence (Cartwright et al 2021;Cartwright et al 2022).…”
Section: Measuring Resiliencementioning
confidence: 99%
“…The phenotypes and functions of leukocytes are influenced by several physiological [14] and pathological factors [15]. Stress and excitement during animal housing represent major environmental factors with significant modulatory effects on the immune system [16]. Studies in several animal species have shown that measurements of many immunological parameters in samples taken from stressed animals can be highly variable, ranging from almost normal baseline to extremely high [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Stress and excitement during animal housing represent major environmental factors with significant modulatory effects on the immune system [16]. Studies in several animal species have shown that measurements of many immunological parameters in samples taken from stressed animals can be highly variable, ranging from almost normal baseline to extremely high [16][17][18][19][20]. Cattle and sheep under short-term stress have shown impaired immune responses [17,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation